The Influence of Peer Groups on the Emotional Maturity of Eighth-Grade Adolescents at Al-Ikhlasiyah Junior High School Sei Buluh Academic Year 2020/2021 - Lwi Sindria Pasaribu; Widya Utami Lubis (Pusdikra-Publishing.com, 2024)
The study aims to investigate the influence of peer groups on the emotional maturity of adolescents in the eighth grade MTs Al-Ikhlasiyah Sei Buluh in the 2020/2021 school year. An unripe emotional condition in adolescents can cause them to be vulnerable to a group of peers in performing certain actions, although not all of them have a positive impact on themselves or others. The research method used is quantitative descriptive with a quantitational approach that emphasizes the analysis of numerical data. The primary data was obtained through the filling of the elevator by the pupils of the eighth grade MTs Al-Ikhlasiyah Sei Ten Years of Education 2020/2021, consisting of 123 students. The sampling technique was performed randomly, with 30 students as samples of research. The results of simple linear regression analysis showed a significant influence between peer groups (X) on adolescent emotional maturity (Y) with a F significance count of 0.055 and a significance level of 0.016 < 0.05. Therefore, it can be concluded that the regression model can be used to predict the participation variable, suggesting that peer groups have an influence on adolescent emotional maturity in Al-Ikhlasiyah Sei Buluh T.A 2020/2021.